Reconstruction after resection of C2 vertebral tumors: A comparative study of 3D-printed vertebral body versus titanium mesh - Hu, Panpan; Du, Suiyong; Wei, Feng; Zhai, Shuheng; Zhou, Hua; Liu, Xiaoguang; Liu, Zhongjun (Frontiers in Oncology, 2022)
Background: Surgical resection of C2 vertebral tumors is challenging owing to the complex anatomy of C2 vertebrae and the challenges to surgical exposure. Various surgical approaches are available, but some are associated with excessively high risks of complications. An additional challenge is reconstruction of the upper cervical spine following surgery. In the last decade, additive-manufacturing personalized artificial vertebral bodies (AVB) have been introduced for the repair of large, irregular bony defects; however, their use and efficacy in upper cervical surgery have not been well addressed. Therefore, in this study, we compared instrumented fixation status between patients who underwent conventional titanium mesh reconstruction and those who underwent the same resection but with personalized AVBs. Methods: We performed a retrospective comparative study and recruited a single-institution cohort of patients with C2 vertebral tumors. Clinical data and imaging findings were reviewed. Through data processing and comparative analysis, we described and discussed the feasibility and safety of surgical resection and the outcomes of hardware implants. The primary outcome of this study was instrumented fixation status. Results: The 31 recruited patients were divided into two groups. There were 13 patients in group A who underwent conventional titanium mesh reconstruction, and 18 group B patients underwent personalized AVBs. All patients underwent staged posterior and anterior surgical procedures. In the cohort, 9.7% achieved total en-bloc resection of the tumor, while gross total resection was achieved in the remaining 90.3%. The perioperative complication and mortality rates were 45.2% and 6.5%, respectively. The occurrence of perioperative complications was related to the choice of anterior approach (P<0.05). Group A had a higher complication rate than group B (P<0.05). Four patients (4/13, 30.8%) developed hardware problems during the follow-up period; however, this rate was marginally higher than that of group B (1/18, 5.6%). Conclusions: Total resection of C2 vertebral tumors was associated with a high risk of perioperative complications. The staged posterior and retropharyngeal approaches are better surgical strategies for C2 tumors. Personalized AVBs can provide a reliable reconstruction outcome, yet minor pitfalls remain that call for further modification.